2014
DOI: 10.1111/evo.12340
|View full text |Cite
|
Sign up to set email alerts
|

PREDICTABILITY AND IRREVERSIBILITY OF GENETIC CHANGES ASSOCIATED WITH FLOWER COLOR EVOLUTION INPENSTEMON BARBATUS

Abstract: Two outstanding questions in evolutionary biology are whether, and how often, the genetic basis of phenotypic evolution is predictable; and whether genetic change constrains evolutionary reversibility. We address these questions by studying the genetic basis of red flower color in Penstemon barbatus. The production of red flowers often involves the inactivation of one or both of two anthocyanin pathway genes, Flavonoid 3 ,5 -hydroxylase (F3 5 h) and Flavonoid 3 -hydroxylase (F3 h). We used gene expression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 70 publications
1
57
0
Order By: Relevance
“…Evolutionary studies of flavonoid production have largely focused on changes in floral anthocyanins, which are key contributors to floral hue (Hopkins and Rausher, 2011;Rausher, 2008;Smith and Rausher, 2011;Wessinger and Rausher, 2014;Whittall et al, 2006). This study shows that these shifts in floral anthocyanins can result in correlated changes in floral flavonols, particularly those at the same hydroxylation level.…”
Section: Discussionmentioning
confidence: 80%
“…Evolutionary studies of flavonoid production have largely focused on changes in floral anthocyanins, which are key contributors to floral hue (Hopkins and Rausher, 2011;Rausher, 2008;Smith and Rausher, 2011;Wessinger and Rausher, 2014;Whittall et al, 2006). This study shows that these shifts in floral anthocyanins can result in correlated changes in floral flavonols, particularly those at the same hydroxylation level.…”
Section: Discussionmentioning
confidence: 80%
“…This QTL corresponds to F3 0 5 0 h, which resides directly under the peak LOD (figure 4). We have previously shown that this gene is responsible for the difference in colour between the two species [13]. For each of the remaining traits, there were three significant QTLs, explaining a total of 45-65% of the total proportion of trait variation.…”
Section: (D) Qtl Mapping Resultsmentioning
confidence: 91%
“…Yet, some empirical evidence from quantitative trait locus (QTL) studies on pollination syndrome divergence suggests that there may be common patterns at the genetic level. For example, previous QTL studies have suggested that traits such as flower colour and nectar volume often involve few substitutions of medium to large effect [9][10][11][12][13], while changes in morphological characters tend to involve more loci with smaller effects [12,14,15]. In addition, these studies have revealed that QTLs for different traits sometimes co-localize (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Anthocyanin are the major water-soluble pigments, produced by the flavonoid biosynthesis pathway, widely distributed in flowering plants and responsible for pink, purple, red, and blue of many flowers and fruits (Chandler & Tanaka, 2007; Wessinger & Rausher, 2014). Currently, all structural genes involved in the anthocyanin synthesis have been well characterized in many species (Schwinn & Davies, 2004; Grotewold, 2006; Guo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%